Discussion on Cross-Cultural Collaboration for Vocational Teacher Education among US and Chinese Institutions - Xi Yu (Adult Education Research Conference, 2014)
This roundtable session is to discuss about the different characteristics of Chinese and US vocational education systems, the challenges of Chinese VET is facing, and the need and barriers for Chinese vocation teacher education collaborating with US institutions.